Eficiência dos sistemas de aproveitamento das águas pluviais na região central do Rio Grande do Sul - Seeger, Lília Mayumi Kaneda (2008)
This work shows a study about the system efficiency of rainwater s usage in the central region of Rio Grande do Sul and it aims to evaluate the utilization of not potable waters´ potential that come from impermeable surfaces. The hydrological potential was classified very good, considering pluvial sources (rainwater) from 30 regions' station, with historical series higher than 15 years. The activities to exploitation and its respectively demands were chosen, determining the efficiency of the system usage, with the use of different areas of captation and commercial volumes of rainwater tanks. The volumetric reliability was calculated in single-family house with the use of daily and monthly precipitation from the historic series of Santa Maria (code 02953034), volumes of 10, 12 and 20 m³ and areas of 70, 100, 150, 200 and 300 m². It was verified that the use of daily or monthly sources (datas) of precipitation conducted to nearest results. There are coincidences to minimum values, including in the dimension of the area s captation and the volume of storage. However, it was observed that to maximum reliability, the volume s results and the areas are bigger when monthly sources (datas) were used. In order to compare the sources, it was analyzed the efficiency applying volumes of water tanks determined by Kobiyama and Hansen Method (2002) to Cacequi´station (code 02954001). In this case, it was also determinated the captation s area that resulted in better volumetric reliability. The comparative analysis between the studied stations showed that there is a significant efficiency s development in function to the increase of the area of captation to the same volume of storage in comparison to a small variation of efficiency to the enlargement to the volume of a constant area. The methodology in this study offers an interconnected vision of the influence of the different constituents of the system usage, simulating the behavior of the system as a whole. The demands of single-family house with area of 70 m2 and water tanks of 500 L the minimum of efficiency found was 20% and the maximum was 28.33%. To multi-store building with area of 300 m² and 15000 L of reservoir s volume, the minimum was 10% and the maximum was 17.33%. In Gas Stations with 1000 m² of area and volume of 20000 L, the minimum volume was 40% and the maximum 58%. In beer s industry with area of 7000 m² and reservoir volume of 20000 L, the results showed minimum of 25% and maximum of 38.65¨%. The method presented makes possible the graphic visualization of the efficiency to be obtained in the usage systems to determine captation area, rainwater tanks volume and the implemented demands. It also allowed to verify the dimension to be projected in relation to captation s area and the volume of storage, since the demands has been determinated to reach and determine the intended efficiency. The equation s adjustment to the reservoir s sizing was obtained from a R2 coefficient adjustment of 0.9925 and from Nash coefficient of 0.9914. The criteria showed and discussed revealed adequate, resulting in efficiencies quite satisfactory to partial demands to not potable waters in the analyzed cities.